Mitochondria: Mitochondrial participation in ischemia–reperfusion injury in skeletal muscle - Lejay, Anne; Meyer, Alain; Schlagowski, Anna-Isabel; Charles, Anne-Laure; Singh, François; Bouitbir, Jamal; Pottecher, Julien; Chakfé, Nabil; Zoll, Joffrey; Geny, Bernard (The international journal of biochemistry & cell biology, 2014)
Irrespective of the organ involved, restoration of blood flow to ischemic tissue is vital, although reperfusion per se is deleterious. In the setting of vascular surgery, even subtle skeletal muscle ischemia contributes to remote organ injuries and perioperative and long-term morbidities. Reperfusion-induced injury is thought to participate in up to 40% of muscle damage. Recently, the pathophysiology of lower limb ischemia–reperfusion (IR) has been largely improved, acknowledging a key role for mitochondrial dysfunction mainly characterized by impaired mitochondrial oxidative capacity and premature mitochondrial permeability transition pore opening. Increased oxidative stress triggered by an imbalance between reactive oxygen species (ROS) production and clearance, and facilitated by enhanced inflammation, appears to be both followed and instigated by mitochondrial dysfunction. Mitochondria are both actors and target of IR and therapeutic strategies modulating degree of ROS production could enhance protective signals and allow for mitochondrial protection through a mitohormesis mechanism.